Representasi Makna Dan Pesan Dalam Lirik Lagu “Sebuah Tarian Yang Tak Kunjung Selesai” Oleh Nadin Amizah Menggunakan Pendekatan Semiotik - Siti Yulia Putri Pratiwi (Universitas Palan, 2023)
This research is motivated by the rise of Nadin Amizah's songs which are difficult for listeners to understand, especially teenagers. Meanwhile, a song is a line of words combined with music and has a meaning or message to be conveyed to listeners. The problem discussed is the meaning and message in the lyrics of the song